Levels of Inquiry-Interactive Demonstration: Its Effect on Students' Critical Thinking Ability in Online Learning with the Topic of Waves and Sounds - Siti Nafingah; Mohamad Agung Rokhimawan; Ali Mustadi; Muhammad Nur Wangid (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2020)
This study aims to determine the effect of Levels of Inquiry-Interactive Demonstration on students' critical thinking ability at UIN Sunan Kalijaga Yogyakarta. This research is a quasi-experimental type with a pretest-posttest control group design. The research sample was taken using a cluster sampling technique. The sample consisted of the experimental class (PGMI A) composed of 41 students using the Inquiry-Interactive Demonstration model. The control class (PGMI B) was composed of 41 students using conventional learning models lecture and assignment methods. The data collection technique used was a test through quizizz, google form, observation, and documentation. The data analysis technique used descriptive statistics which were, preceded by a normality test. Hypothesis testing using the T-test. The results showed that the pretest-posttest mean score increased, namely the pre-test 68.49 and the post-test 85.27 with Tcount 11.95 > Ttable 2.023. Then the results of the sig value. 0.000 < 0.05 means that using the Inquiry-Interactive Demonstration model has a significant effect on students' critical thinking abilities on the topic of waves and sound.